2021
DOI: 10.26434/chemrxiv.14483457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Edge-Hydrogenated Germanene by Electrochemical Decalcification-Exfoliation of CaGe2: Germanene-Enabled Vapor Sensor

Abstract: <p><a>Two-dimensional germanene has been recently explored for applications in sensing, catalysis, and energy storage. The potential of this material lies on its graphene-like optoelectronic and chemical properties. However, pure free-standing germanene cannot be found in nature and the synthetic methods are hindering the potentially fascinating properties of germanene. </a>Herein, <a>we report for the first time a single-step synthesis of few-layer germanene by electrochemical exfoliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The results showed that germanane nanosheets are highly sensitive to volatile organic compounds (VOCs), the biomarker, indicating that germanane nanosheets can be used as molecular devices for detecting liver cirrhosis VOCs (Figure 25E). The most recent work by Kovalska et al 573 demonstrated the edge hydrogenation of germanene by electrochemical decalcification‐exfoliation of CaGe 2 , enabling germanene specific sensitivity to organic vapors, showing selectivity to methanol over ethanol as a sensor. This result confirms the potential of Ge‐based 2D materials as gas sensors.…”
Section: Applications Of Ge‐based 2d Materialsmentioning
confidence: 99%
“…The results showed that germanane nanosheets are highly sensitive to volatile organic compounds (VOCs), the biomarker, indicating that germanane nanosheets can be used as molecular devices for detecting liver cirrhosis VOCs (Figure 25E). The most recent work by Kovalska et al 573 demonstrated the edge hydrogenation of germanene by electrochemical decalcification‐exfoliation of CaGe 2 , enabling germanene specific sensitivity to organic vapors, showing selectivity to methanol over ethanol as a sensor. This result confirms the potential of Ge‐based 2D materials as gas sensors.…”
Section: Applications Of Ge‐based 2d Materialsmentioning
confidence: 99%